The vegetation of the Sárrét basin of Fejér county in the late-pleistocene and holocene - Molnár, Marianna; Czóbel, Szilárd; Medzihradszky, Zsófia; Barczi, Attila (JOURNAL OF LANDSCAPE ECOLOGY, 2013)
The drilled sample obtained from Sárrét of the Fejér County in Hungary was divided by 5 – 10 centimeters long intervals and 41 samples were selected among them for analyzing. According to these samples 5 pollen zones (LPAZ) could be defined. The first two zones reflect the climate change happened during the Pleistocene and the Holocene in the investigated area. This data helped us to reconstruct the former vegetation and understand the details of the climate changes occurred in the recent thousands of years. Since we could not date the samples by radiocarbon methods each zone was dated back based on previous palinological and malacological studies (WILLIS et al. 1997, SÜMEGI et al. 2007). The goal of our research was to extend previous analysis carried out in this area earlier with newer data sets. In the future we are also intending to perform more detailed analysis regarding the climate change and the former vegetation based on the recently drilled out core samples obtained from the same area.